Outcome of laparoscopic vs open appendectomy in the management of acute appendicitis (Nepal Medical College Journal, 2023)
The worldwide trend of appendectomy is shifting from conventional open to the laparoscopic technique. The study’s objective was to compare laparoscopic and open appendectomy in terms of various operative and postoperative parameters to find the best operative technique. A prospective comparative study was conducted on 142 patients undergoing laparoscopic (n=43) or open appendectomy (n=99) from 1st February 2022 to 30th January 2023 under the Department of Surgery of Kathmandu Medical College Teaching Hospital (KMCTH). In five patients, laparoscopic appendectomy was later converted to open and excluded from the study. The mean operating time for the open appendectomy group was 44.1±13.1 minutes while for the laparoscopic appendectomy group, it was 48.4±14.0 minutes (p=0.047). Visual analogue score taken on 1st, 7th and 30th post-operative day for open and laparoscopic appendectomy were 4.0±2.2 vs 3.6±1.9 (p=0.160); 1.4±1.3 vs 0.6±0.9 (p